Bilateral phyllodes tumor: Case report - Isabel Mayorga-Pérez; Patricia Mulero-Soto; Kerwin Cruz-De La Rosa; Viviana Negrón-González; Jonathan Hernandez-Rosa; Jose Feneque-Gonzalez; Maria Correa-Rivas; Anwar Abdul-Hadi (Elsevier, 2024)
Introduction: Phyllodes tumors are rare fibroepithelial neoplasms. They represent less than 0.5-1% of all primary breast tumors and their presentation is even rarer in children. Case description: A 15-year-old female with Autism Spectrum Disorder (ASD) was seen in the outpatient surgery clinic due to bilateral breast masses. She underwent core-needle aspiration. biopsy of both masses and the results were suspicious of fibroadenomas. Two days later the patient presented to the emergency room with ulceration and bleeding from the left breast mass. She was scheduled for an urgent nipple-sparing mastectomy, which was uneventful. The pathology revealed a multifocal, aggressive type tumor with moderate stromal cellularity, moderate stromal atypia and high mitotic index, corresponding to a borderline phyllodes tumor. Based on this result, she underwent an elective right nipple-sparing mastectomy. The pathology of the right breast mass was similar to the left breast mass. Conclusion: Core-needle aspiration biopsy is not reliable for the diagnosis of phyllodes tumor. If a phyllodes tumor is diagnoses in one breast, a contralateral breast mass should be considered a phyllodes tumor until proven otherwise.